Optimalisasi Penggunaan Konten Bahasa Iklan yang Menarik dalam Membangun Kembali Bisnis di Era New Normal - Mirsa Umiyati (Scopus ID: 57205029801) (Warmadewa Press, 2020)
In its development, small businesses that have been running in the acacia road area, are relatively well run and much in demand by the surrounding community. However, COVID-19 pandemic forced small businesses to temporarily stop their businesses. As a result, the business climate has become sluggish and devoid of trading activities. With the vacuum caused by the pandemic, when small entrepreneurs want to reopen their businesses, a special strategy is needed to be able to attract buyers' interests so that businesses in the new normal era can run smoothly again. So that this community service was built to provide training to small entrepreneurs on the acacia road, to be able to optimize the use of good and attractive Advertising language to achieve the objectives in the above exposure. The method used in optimizing businesses in the new normal era through optimization of advertising language content is the pattern of assisting small entrepreneurs in creating product/service banner advertisements, FGDs and core activities in the form of training in making good advertisements in the form of banners to attract consumers' interest in buying products/services offered.